Achieving High Dialysis Dose via Continuous Renal Replacement Therapy in the Setting of Metformin Associated Lactic Acidosis. A Case Series. Issue 1 (18th January 2022) - Reynolds, Hannah V.; Pollock, Hamish H. G.; Apte, Yogesh V.; Tabah, Alexis
Abstract : Severe and life-threatening cases of metformin-associated lactic acidosis (MALA) are treated with renal replacement therapy. Intermittent hemodialysis is recommended, as it achieves rapid more elimination of metformin compared to continuous renal replacement therapy (CRRT). This case series describes 4 patients, 2 with acute metformin intoxications and 2 with insidious metformin toxicity. All were treated using a novel approach with dual CRRT to achieve rapid elimination of metformin. Three of the 4 patients survived to hospital discharge. Dual CRRT may be an effective alternative when dialysis is not readily available.